Antibacterial and cytocompatible silver coating for titanium Boston Keratoprosthesis - Gómez, Silvia González; Ginebra, Maria-Pau; Gil, Francisco Javier; Barraquer, Rafael I.; Manero, José María (Frontiers in Bioengineering and Biotechnology, 2024)
keratoprosthesis (BKPro) 1 , Corneal blindness 2 , Titanium (Ti) 3 , Infection 4 , Antibacterial properties 5 , Electrodeposition 6 , Cytotoxicity 7 , Silver deposition 8The Boston Keratoprosthesis (BKPro) is a key medical device for restoring vision in cases of severe corneal blindness. However, a significant challenge for its long-term success lies in the risk of infection, with rates ranging from 3.4 % to 17.3 %. Surprisingly, only a few studies have explored infection-preventing mechanisms for the BKPro. In this study, we introduce a novel approach utilizing silver ions to enhance the antibacterial properties of the titanium backplate of the BKPro. While silver ions are recognized for their antibacterial properties, their application in corneal implants remains unexplored. Our research employs a unique electrodeposition technique to securely attach silver complexes to the titanium surfaces, achieving bactericidal effects without harming the corneal tissue. The obtained results are significant as they demonstrate the effectiveness of this approach in preventing bacterial infections commonly associated with BKPro. Moreover, our research proposes the mechanisms by which silver ions combat bacteria, providing valuable insights for future advancements in implant design and infection prevention. This work not only addresses a critical issue in the field of ophthalmology and also opens new avenues for improving the safety and longevity of corneal implants.